Bioremediation of Uranium- and Nitrate-Contaminated Groundwater after the In Situ Leach Mining of Uranium - Rehemanjiang Wufuer (MDPI AG, 2021)
Uranium and nitrate are common groundwater pollutants near in situ leach uranium mines. However, we still lack techniques that can simultaneously immobilize uranium and reduce nitrate using a single bacterial species. In this study, the potential of simultaneous uranium immobilization and nitrate reduction by a single AFODN (anaerobic Fe(II) oxidizing denitrifier), Clostridium sp. PXL2, was investigated. Clostridium sp. PXL2 showed tolerance to U(VI) concentrations varying from 4.2 µM to 42 µM. The U(VI) immobilization and nitrate reduction rates in groundwater samples inoculated with this bacterium reached up to 75.1% and 55.7%, respectively, under neutral conditions. Exposure to oxidation conditions led to further U(VI) removal but did not show any noticeable effect on nitrate reduction. The U(VI) immobilization rate reached up to 85% with an increased Fe(II) initial concentration, but this inhibited nitrate reduction. SEM (scanning electron microscopy) coupled with EDS (energy dispersive spectroscopy) showed that the U(VI) immobilization was mainly due to sorption to amorphous ferric oxides. U(VI) and nitrate bioremediation by AFODNs, including Clostridium sp. PXL2, may provide a promising method for the treatment of uranium- and nitrate-contaminated groundwater after the in situ leach mining of uranium.